Designing disposable hand-made screen-printed electrode using conductive ink for electrochemical determination of dopamine - Dokur, Ebrar; Uruc, Selen; Kurteli, Rabianur; Gorduk, Ozge; Sahin, Yucel (SPRINGER HEIDELBERG, 2023)
In this work, we detailed the improvement of a hand-made screen-printed electrode (SPE), which has easy production with conductive ink. The preparation of the hand-made SPE based on conductive ink to be transferred to cardboard substrates as electrochemical sensors. Thanks to its advantages such as being cheap and easy to obtain, cardboard was preferred as a substrate. As a new approach, we report for the first time in the literature the alkaline pretreatment applied for the cardboard substrate. The conductive ink was used as a working electrode, a counter electrode, and a reference electrode. The components of the developed conductive ink are carboxymethyl cellulose (CMC) as binder, water:ethanol:ethylene glycol as solvent and graphite as conductive material. The SPE was characterized by Fourier-transformed infrared spectroscopy, scanning electron microscopy energy-dispersive X-ray spectroscopy, cyclic voltammetry, and electrochemical impedance spectroscopy. The developed electrode was used in the voltammetric determination of dopamine, an important neurotransmitter for human health. The device achieved a linear response between 5.0 and 1000 mu M and a limit of detection (LOD) of 1.25 mu M. Thus, these developed hand-made SPE was used in the determination of dopamine in a selective, fast, and cost-effective way. It provides a new device approach for electrochemical biosensors and wearable technologies with hand-made screen-printed electrodes developed as easy to prepare, inexpensive and disposable.
Keywords: Conductive ink; Dopamine; Screen-printed electrode; Voltammetry; Neuroscience; REDUCED GRAPHENE OXIDE; ASCORBIC-ACID; FLEXIBLE ELECTRONICS; SENSOR; BINDER; CHALLENGES; OXIDATION; SYSTEM; DEVICE; WATER; Chemistry; Electrochemistry; Physics